Pendidikan Karakter Dalam Pembangunan Keberadaban Bangsa - Ni Made Ratnadi (Kamaya: Jurnal Ilmu Agama, 2021)
Character must be consciously built and developed day by day with a process that is not instantaneous. Character is not something innate that cannot be changed again like a fingerprint. Many people with bad character tend to blame their situation. They often claim that the way they were raised is wrong, financial difficulties, the treatment of other people or other conditions that made them who they are. In life, many things are faced and many things happen out of control, but character is not the case. Character is always the result of choice, and know that everyone has the potential to become a person with character, and that must be done in order to happen. Character is more than anything and will make someone who has more added value. Character will protect everything that is valued in this life. Everyone is responsible for their character. A person must have complete control over his character, meaning that one cannot blame others for his bad character because he is fully responsible. Developing character is a personal responsibility.